2013
DOI: 10.1016/j.chb.2013.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Video game training to improve selective visual attention in older adults

Abstract: The current study investigated the effect of video game training on older adult’s useful field of view performance (the UFOV® test). Fifty-eight older adult participants were randomized to receive practice with the target action game (Medal of Honor), a placebo control arcade game (Tetris), a clinically validated UFOV training program, or into a no contact control group. Examining pretest–posttest change in selective visual attention, the UFOV improved significantly more than the game groups; all three interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
86
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 29 publications
(51 reference statements)
8
86
0
2
Order By: Relevance
“…The remaining 37 articles all reported high percentages of female participants, thus being the majority of the gender split. The study setting/context varied widely across the 46 articles and was composed of retirement/independent communities 11,12,14,21,24,26,29,32,39,40,42,44,47,48,53 (n = 15), communitydwelling 13,16,19,45,46,49 (n = 6), community center 20,31,38,51,52 (n = 5), hospital/assisted living/residential/nursing home/longterm care/institutionalized 10,[15][16][17][18]25,27,28,30,33,35,37,41,43,50,54 (n = 16), not specified 23 (n = 1), or other 34,36,55 (n = 3). The majority of the studies were primarily conducted across two different living environments (hospital/assisted living/residential/nursing home/long-term care/institutionalized) or reti...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 37 articles all reported high percentages of female participants, thus being the majority of the gender split. The study setting/context varied widely across the 46 articles and was composed of retirement/independent communities 11,12,14,21,24,26,29,32,39,40,42,44,47,48,53 (n = 15), communitydwelling 13,16,19,45,46,49 (n = 6), community center 20,31,38,51,52 (n = 5), hospital/assisted living/residential/nursing home/longterm care/institutionalized 10,[15][16][17][18]25,27,28,30,33,35,37,41,43,50,54 (n = 16), not specified 23 (n = 1), or other 34,36,55 (n = 3). The majority of the studies were primarily conducted across two different living environments (hospital/assisted living/residential/nursing home/long-term care/institutionalized) or reti...…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies did not integrate the oldest old as a meaningful proportion of the sample, despite the increasing [10][11][12]14,17,[21][22][23][24][25][28][29][30][31][32][33][34][35][36][37][38][39][40]42,[44][45][46][47][48][49][50][51][52][53][54] To clarify sample proportions and enable our analysis, two authors contacted the respective authors seeking further clarification of the actual number of participants q85 years of age when necessary. Consistent with previous reviews, 2-5 this study highlights a substantial gap in the knowledge base and encourage further exploration into digital gaming use in those 85 years of age and greater.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in research to promote cognitive enhancement (e.g. Belchior et al, 2013; Okagaki & Frensch, 1994), treat amblyopia or ‘lazy eye’ (Li et al, 2013), dampen vividness, and emotionality of autobiographical memories (Engelhard, van Uijen, & van den Hout, 2010), reduce cravings (Skorka‐Brown, Andrade, & May, 2014; Skorka‐Brown, Andrade, Whalley, & May, 2015), prevent intrusive memories of psychological trauma (Holmes, James, Coode‐Bate, & Deeprose, 2009; Iyadurai et al, 2017; James et al, 2015; James, Lau‐Zhu, Tickle, Horsch & Holmes, 2016b), and lessen mania‐related mental images (Davies, Malik, Pictet, Blackwell, & Holmes, 2012). Little is currently known about the cognitive mechanisms underpinning the benefits of Tetris, but one hypothesis emerging from the clinical psychology literature is that it selectively taxes visuospatial working memory (WM; Holmes et al, 2009; James et al, 2015).…”
mentioning
confidence: 99%
“…Evidence suggests that it activates regions of the brain associated with visuomotor processes, including sensory‐motor cortical dynamics (Rietschel et al, 2012) and occipitoparietal brain regions (Price, Paul, Schneider, & Siegle, 2013). Cognitive training studies have also shown benefits on visuospatial tasks following repeated practice on Tetris, with improvements observed in spatial ability (Okagaki & Frensch, 1994; Terlecki, Newcombe, & Little, 2008), mental rotation (De Lisi & Wolford, 2002; Moreau, 2013) and selective visual attention (Belchior et al, 2013; Green & Bavelier, 2003). Tetris game play can also lead to hypnagogic visual hallucinations that mix Tetris‐shape representations with other memories — the so call ‘Tetris effect’ (Kusse, Shaffii‐LE Bourdiec, Schrouff, Matarazzo, & Maquet, 2012; Stickgold, 2000).…”
mentioning
confidence: 99%
“…Some evidence exists for the notion that cognitive benefits can be obtained by training non-gamers on action video games (Green & Bavelier, 2003) even when the participants are older adults (Anguera et al, 2013;Belchior et al, 2013). Yet, such training studies have also produced null findings (Boot et al, 2008).…”
Section: Introductionmentioning
confidence: 99%